Repeated versus single praziquantel dosing regimen in treatment of female genital schistosomiasis: a phase 2 randomised controlled trial showing no difference in efficacy - Arenholt, Louise Thomsen Schmidt; Randrianasolo, Bodo Sahondra; Rabozakandraina, Tiana Onintsoa Oliva; Ramarokoto, Charles Emile; Jøker, Karoline; Kæstel Aarøe, Katrina; Brønnum, Dorthe; Bundgaard Nielsen, Caspar; Sørensen, Suzette; Lumholdt, Mads; Jensen, Martin; Lundbye-Christensen, Søren; et al. (Frontiers in Tropical Diseases, 2024)
BackgroundSingle-dose praziquantel (PZQ) for treating urogenital schistosomiasis has been reported as inadequate for achieving significant resolution of female genital schistosomiasis (FGS)-associated cervicovaginal lesions. This randomised controlled trial aimed to assess the efficacy and safety of a repeated PZQ-dosing regimen.MethodsThe trial was conducted among women aged 15 to 34 with FGS-associated cervical lesions living in a Schistosoma haematobium-endemic area of northern Madagascar. A total of 116 women were randomly allocated to either repeated PZQ-dosing (n=58) or a single PZQ dose (n=58). All received an initial PZQ dose of 40mg/kg at baseline. In the repeated-dosing arm, additional doses were given 12 and 24 hours later and again at 5 and 10 weeks. Primary outcome was FGS-related cervical lesions at baseline compared to Week 15 follow-up. Secondary outcomes encompassed pelvic exam abnormalities, urogenital complaints, and biomarkers, including cervicovaginal S. haematobium DNA and circulating anodic antigens (CAA) in serum.ResultsExcluding 21 women who were pregnant or failed to attend follow-up visits, 95 women were eligible for per-protocol treatment effect analysis. A minor and insignificant reduction in cervical lesions was observed in both of the two treatment arms at Week 15 follow-up. A clear tendency towards decline in pelvic exam abnormalities and urogenital complaints in both treatment arm groups was observed. The reduction in number of women testing positive for CAA and mean CAA values was significant in both arms but less so in the single-dose arm. Mild to moderate adverse events of equal proportions were reported in both treatment arm groups.ConclusionFGS-associated cervical lesions appear refractory to PZQ treatment even when this is administered in a repeated-dosing regimen. In contrast, the repeated regimen seems more effective at eliminating the dwelling worm population than the single-dose regimen, as demonstrated by the CAA findings. Irrespective of dosing regimen, pelvic exam abnormalities and urogenital complaints saw equal reductions at follow-up. However, the outcome of our primary study emphasises the need for initiation early in life and a persistently maintained PZQ treatment strategy throughout childhood and adolescence to prevent lesions from establishing in the first place.Clinical trial registrationhttps://clinicaltrials.gov/, dentifier NCT04115072.